2023
DOI: 10.1177/09726527231197328
|View full text |Cite
|
Sign up to set email alerts
|

IFRS and ESG Disclosure in Indian Corporate Sector

Ajit Dayanandan,
Han Donker,
Sudershan Kuntluru

Abstract: World-wide, there is movement toward embracing environmental, social, and governance (ESG) issues in corporate conduct and performance. These developments have led to movement toward “reimagining capitalism,” and many firms have ridden the wave of investor enthusiasm for firms that prioritize ESG disclosures. The present study examines the role of International Financial Reporting Standards (IFRS) in India on ESG and overall ESG reporting. The Indian capital markets regulator, SEBI, had made integrated reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The complex relationship between Environmental, Social, and Governance (ESG) factors and firm value has been the subject of extensive research [13,14,29,[33][34][35][36]. Through rigorous analysis, studies have demonstrated that higher ESG disclosure scores have a significant positive impact on firm value [4,11,37], innovation performance [35,36], and cost of equity capital [38].…”
Section: Firm's Esg Disclosure and Market Valuementioning
confidence: 99%
“…The complex relationship between Environmental, Social, and Governance (ESG) factors and firm value has been the subject of extensive research [13,14,29,[33][34][35][36]. Through rigorous analysis, studies have demonstrated that higher ESG disclosure scores have a significant positive impact on firm value [4,11,37], innovation performance [35,36], and cost of equity capital [38].…”
Section: Firm's Esg Disclosure and Market Valuementioning
confidence: 99%